A simple aggregate demand analysis with dynamic optimization in a small open economy - Ken-ichi Hashimoto; Yoshiyasu Ono (Osaka University, Institute of Social and Economic Research (ISER), 2019)
We develop an aggregate demand analysis of a small open economy based on all agents' dynamic optimization. Murota and Ono (2015) present a simple Keynesian cross analysis with dynamic optimization. This paper extends it to a small-country setting with two factors and two commodities, of which the structure is as simple as the conventional Keynesian cross analysis. We apply the model to examine the effects of changes in various parameters, such as the terms of trade, foreign asset holdings and government purchases, on aggregate demand. They are quite different from those under full employment and those of the Mundell-Fleming model.
Keywords: E12; E13; E21; E24; F32; F41; 330; aggregate demand shortage; unemployment; small open economy